2022
DOI: 10.1007/s41748-022-00335-9
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Salinity and Water Management Practices in the Bengal Delta: A Critical Analysis to Inform Salinisation Risk Management Strategies in Asian Deltas

Abstract: Salinisation within delta environments is a dynamic process governed by the interaction between coastal, fluvial and geomorphological systems. Increasingly, these have been modified through human activity and management practices, which lead to unintended problems associated with waterlogging and salt accumulation in soils and water resources. As a result of these issues, over 100 million people in the Ganges–Brahmaputra and other Asian deltas are negatively affected by a lack of freshwater availability and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 104 publications
(191 reference statements)
0
2
0
Order By: Relevance
“…Previous research in low-lying Asian mega-deltas (Figure 1) has suggested a range of factors influencing the salinity of surface waters and groundwater (Yu et al, 2010;Salehin et al, 2018;Akter et al, 2019Akter et al, , 2020Sherin et al, 2020;Bricheno et al, 2021;Feist et al, 2023;Raff et al, 2023). These include: (i) changes in the magnitude and seasonality of upstream river discharge and sediment deposition; (ii) subsidence, sea-level rise (SLR) and seasonal tidal fluctuations; and (iii) the intensity and frequency of tropical cyclones and storm surges.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research in low-lying Asian mega-deltas (Figure 1) has suggested a range of factors influencing the salinity of surface waters and groundwater (Yu et al, 2010;Salehin et al, 2018;Akter et al, 2019Akter et al, , 2020Sherin et al, 2020;Bricheno et al, 2021;Feist et al, 2023;Raff et al, 2023). These include: (i) changes in the magnitude and seasonality of upstream river discharge and sediment deposition; (ii) subsidence, sea-level rise (SLR) and seasonal tidal fluctuations; and (iii) the intensity and frequency of tropical cyclones and storm surges.…”
Section: Introductionmentioning
confidence: 99%
“…These include: (i) changes in the magnitude and seasonality of upstream river discharge and sediment deposition; (ii) subsidence, sea-level rise (SLR) and seasonal tidal fluctuations; and (iii) the intensity and frequency of tropical cyclones and storm surges. In the Bengal Basin of Bangladesh, surface water salinity regimes are also locally influenced by land-use change and human interventions such as coastal embankments known locally as "polders, " shrimp farming, and dry-season irrigation from surface waters and wells (Ayers et al, 2017;Islam et al, 2019;Shamsudduha et al, 2022;Feist et al, 2023). The complex interplay of these different factors makes it challenging to identify the primary drivers of saltwater intrusion over large, complex low-lying deltaic systems (Bricheno et al, 2021;Feist et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This example demonstrates the need for rapid response to pond salinization (pond salinities with no remediation and remediations were compared in Fig. 4 d) in order to ensure low salinity pond drinking water in southern Bangladesh, and probably in other deltaic coasts in Asia 22 , 37 as well. The need for rapid responses to polder and pond management is likely to become even more critical in future years as climate change results in projected increases in tropical cyclone intensity and frequency 24 , 25 , 38 , as explored below.…”
Section: Resultsmentioning
confidence: 97%
“…Use of Microwave radar data, exhibits accurate sensitivity to the dielectric constant for salt-affected soils and the ability to penetrate is independent of environmental factors. Numerous experimental studies (Hilhorst et al, 1998;Feist et al, 2023) have been carried out over the past using interfacial polarization mechanisms affecting dielectric soils behaviour at low to medium frequencies. Furthermore, several tools have been developed to demonstrate that the dielectric constant (DC) of a soil depends on its volumetric moisture content (Periasamy, 2020;Wang et al, 2016) in semi-arid regions.…”
Section: Introductionmentioning
confidence: 99%